PENATAAN LEMBAGA NEGARA PENUNJANG INDEPENDEN DALAM SISTEM KETATANEGARAAN INDONESIA - Zamroni, Muchammad; Nugroho, Jati; Ibrahim, Anis; Purwanti, Henny; Sriyantini , Dwi (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2025)
The atmosphere of the check and balances relationship in the Trias Politica between state agencies tests each other because each state agency may not exceed the limits of power that have been determined by the laws and regulations of state agencies, their powers are not interfered with so that there is a balance of power between state agencies. Through a normative legal approach related to the arrangement of independent supporting state institutions, it can be concluded as follows: First, looking at the level or hierarchy of laws and regulations that regulate independent state institutions, the higher the laws and regulations that underlie their formation such as the National Human Rights Commission, the General Elections Commission, the Corruption Eradication Commission and other state institutions that have what is called constitutional importance, the more independent the institution is. Second, looking at the functions carried out by independent supporting institutions, these state institutions can also be grouped based on the functions inherent in the institution, such as institutions that carry out judicial functions based on Article 24 paragraph (3) such as: the Corruption Eradication Commission, the Prosecutor's Office, and the National Police, Executive functions such as the National Human Rights Commission, legislative functions such as the Financial Transaction Reports and Analysis Center, and the Indonesian National Police. Keywords: Arrangement of State Institutions, Independent Supporters, State Administration System